Transition to 12-year model of education in Kazakhstan: creation of russian textbooks (Eurasian Journal of Philology Science and Education, 2015)
This article specifies the purposes and problems of the National program for education development in the Republic of Kazakhstan for 2011 - 2020 on modernization of system of secondary education – to transition to 12-year model of training are considered. It assumes development and deployment of the new standard of the education based on competence-based approach. Because by 2015 1, 5 and 11 classes of comprehensive schools of Kazakhstan will be transferred to 12-year model of training, groups of authors were faced by a task to create new educational and methodical complexes in different subjects for these classes of comprehensive schools of the natural and mathematical and public and humanitarian direction. Problems of training in Russian, set according to the Training program authors of article in the educational and methodical complexes created by them for an experimental 11th class of the public and humanitarian and natural and mathematical direction (Almaty: Mektep, 2013), their structure and the contents are analyzed. Conclusions: Feature of educational and methodical complexes is practice-and-field oriented training in Russian on a text basis. Text-and-centric approach to studying of language consists in the analysis of all language phenomena from the point of view of their functioning in the text. The maintenance of a training material allows to carry out within each subject development of speech-communicative abilities by means of work with coherent written and oral texts, and also to systematize knowledge of language and speech.
Keywords: National program for education development; transition to the 12-year model of education; the Russian textbook for the 11th class.